TOTAL AND DIFFERENTIAL LEUKOCYTE COUNT IN HEALTHY NEWBORNS - Kumar, Ashwani; Yadav, Meetu; Charan, Gopal Singh; SARANGAL, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to establish normal reference values of total and differential leukocyte count (DLC) in Indian neonatal population. Methods: The study was conducted on 200 healthy newborns admitted to neonatology section of Department of Paediatricsa. Maternal and Neonatal data was recorded on a pretested pro forma. Thin-layer chromatography (TLC) was done by manual method (hemocytometer method) using improved Neubauer Chamber. For calculating DLC smear was made from the EDTA blood and was stained by Leishman stain (Romanowsky group). DLC was done in body and tail part of the stained smears by following Z pattern. Statistical Analysis: Descriptive statistical analysis was carried out in the present study. Mean, standard deviation, t-test, and analysis of variance tests were used to test the significance of the differences among sample means. Results: Mean TLC at various period of gestations were 4500/cumm at 31 weeks, 7627±2320/cumm at 33 weeks, 8325±1943/cumm at 34 weeks, 8141±1538/cumm at 35 weeks, 8455±904/cumm at 36 weeks, 8840±658/cumm at37 weeks, 9380±896/cumm at 38 weeks, 10143±1369/cumm at 39 weeks, 9155±2444/cumm at 40 weeks, and 11750±353/cumm at 41 weeks. Conclusion: TLC showed increase with gestation except at 35 weeks and 40 weeks. Neutrophils shows increase with gestation except at 35 weeks and 40 weeks lymphocytes shows increase with gestation except at 34 weeks, 39 weeks, and 40 weeks.